The Implementation of Child Care Service Standards at UPT Social Services for Children and the Elderly Siborongborong North Tapanuli: - - Sarah Pebriana Lumbantoruan; Mia Aulina Lubis S.Sos., M.Kesos; Dra. Berlianti M.SP (International Journal of Educational Technology Research, 2023)
Every human being has the right to an adequate standard of living, and a child is no exception. As a concrete manifestation of the government's efforts and concern in overcoming the problem of neglect, the government established LKSA such as Pelsos Anak which is a solution for parenting services by providing a place for abandoned and underprivileged children. This study aims to determine the Implementation of Child Care Service Standards conducted by UPT Pelsos Anak dan Lansia in Siborongborong District, North Tapanuli and uses qualitative research methods with descriptive types. This research data was obtained through interviews, observation, and documentation. The results of this study concluded that the implementation of childcare services was in accordance with Permensos No. 30 of 2011 concerning National Standards for Child Care for LKSA and in the implementation of childcare service programs was in accordance with the theory of Program Implementation according to David C. Korten.